1997
DOI: 10.2307/1131854
|View full text |Cite
|
Sign up to set email alerts
|

The Academic Achievement of Adolescents from Immigrant Families: The Roles of Family Background, Attitudes, and Behavior

Abstract: The goal of this study was to determine the relative impact of family background, parental attitudes, peer support, and adolescents' own attitudes and behaviors on the academic achievement of students from immigrant families. Approximately 1,100 adolescents with Latino, East Asian, Filipino, and European backgrounds reported on their own academic attitudes and behaviors as well as those of their parents and peers. In addition, students' course grades were obtained from their official school records. Results in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
404
3
15

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 256 publications
(447 citation statements)
references
References 5 publications
25
404
3
15
Order By: Relevance
“…In conclusion, a growing body of research shows that adolescents from Latin American and Asian backgrounds are some of the most academically motivated students in the United States (Fuligni 1997); yet, their achievement levels do not always match their motivational aspirations. One major source of their motivation derives from their values of family obligation, their sense to support, respect, and help their family (Fuligni 2001;Tseng 2004).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In conclusion, a growing body of research shows that adolescents from Latin American and Asian backgrounds are some of the most academically motivated students in the United States (Fuligni 1997); yet, their achievement levels do not always match their motivational aspirations. One major source of their motivation derives from their values of family obligation, their sense to support, respect, and help their family (Fuligni 2001;Tseng 2004).…”
Section: Discussionmentioning
confidence: 95%
“…In addition, adolescents from Latin American and Asian backgrounds often feel that trying hard in school is an obligation to their family, and they believe in the usefulness of education for both themselves and their family (Fuligni 1997;Suarez-Orozco and Suarez-Orozco 1995;Suarez-Orozco 1991). Adolescents from immigrant families often believe that they can repay their parents for the sacrifices they made in coming to the United States by succeeding in school (Suarez-Orozco and Suarez-Orozco 1995).…”
Section: Family Assistance and Academic Achievementmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has shown that immigrant adolescents, particularly those from Asia, perform as well as if not better than native-born children (e.g., Caplan, Choy, & Whitmore, 1991;Fuligni, 1997;Kao & Tienda, 1995;Rumbaut, 1994). In contrast, the performance of some children, for example those from Latin America, tends to overlap with or fall below that of native-born children (Conchas, 2001;Kao & Tienda, 1995;Portes & Zhou, 1993;Rumbaut, 1995;Suárez-Orozco & Suárez-Orozco, 1995).…”
mentioning
confidence: 99%
“…This is most likely the case because immigrant parents hold high expectations for their children because they see education as a means to social acculturation and economic success, and these higher expectations are related directly or indirectly with students' educational achievement (Sue and Okazaki 1990). In fact, previous evidence shows that first-and second-generation immigrant students received higher grades in mathematics and English than their nativeborn coethnic peers (Fuligni 1997). Latino/a families may also approach education differently than many families of other ethnoracial students, especially middle class whites (Espinosa 1995).…”
Section: Latino Students' Linguistic Divergence and Immigrant Optimismmentioning
confidence: 99%